2018
DOI: 10.12688/wellcomeopenres.14674.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the cultural meanings of stroke in the Ghanaian setting: A qualitative study exploring the perspectives of local community residents

Abstract: Stroke has undergone different medical constructions over the Background: years. While the medical profession posits that disease is a biological condition, universal and unchanging, social constructionists perceive illness as the social meaning of the biological condition. Even though the medical notion of stroke is monolithic and sometimes contradicts the representations by local community residents, little attention has been paid to understanding the cultural meanings of stroke. This study explores the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Consistent with the findings from this study, the need for stroke awareness campaigns in LMICs is increasingly being advocated by recent studies . Even among health‐care providers in Africa, identifying early stroke symptoms can sometimes be a challenge at the population level .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the findings from this study, the need for stroke awareness campaigns in LMICs is increasingly being advocated by recent studies . Even among health‐care providers in Africa, identifying early stroke symptoms can sometimes be a challenge at the population level .…”
Section: Discussionsupporting
confidence: 87%
“…42 Consistent with the findings from this study, the need for stroke awareness campaigns in LMICs is increasingly being advocated by recent studies. 43,44 Even among health-care providers in Africa, identifying early stroke symptoms can sometimes be a challenge at the population level. 45 Improving the public's knowledge of stroke risk factors, signs and symptoms of stroke is critical to improving the quality of stroke care.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ghanaian context, the coordination of stroke care after discharge from acute care is fragmented ( 34 ), with further rehabilitation after acute care poorly addressed due to accessibility of care issues such as inadequate medical facilities and financial constraints ( 34 , 35 ). For this reason, some patients and/or their caregivers choose to use rehabilitation in a complementary or conventional setting as a treatment for stroke based on availability in the community and acceptability to their health beliefs or religious faith ( 7 , 36 ), and sometimes as a substitute for the absence of conventional rehabilitation ( 7 , 37 ). However, there is a paucity of information on the outcomes of stroke patients who use complementary medicine and rehabilitation in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Although well-established evidence of an increasing stroke burden in Ghana is evident in high mortality and disability rates, 1,2 management of stroke in the healthcare settings is challenging and complex due to the pluralistic healthcare-seeking behaviours 3,4 and a host of factors, including poor healthcare accessibility. [4][5][6] Existing discrepancies between explanatory models of stroke by laypeople and pluralistic healthcare providers contribute to poor stroke prognosis in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Studies have particularly shown that stroke survivors seek biomedical treatment, in addition to treatments from faith healers and herbal/traditional healers, either concurrently or sequentially. 3,4 Despite this, no previous scholarly attempt has been made to report evidence of stroke care, treatment and strategies for improvement from the perspectives of policymakers, health advocates/activists, healthcare professionals as well as faith healers and herbal healers.…”
Section: Introductionmentioning
confidence: 99%